Evolution of infectious diseases induced by epidemic prevention publicity and interaction between heterogeneous strains - Yike Lv; Xinzhu Meng (Electronic Research Archive)
The spread of viruses can be effectively reduced by the publicity of epidemic prevention. Additionally, the interaction between heterogeneous strains has a significant effect on virus evolution. Thus, we first establish an evolutionary dynamics Susceptible-Infected- Recovered (SIR) model which considers the interaction between heterogeneous strains. We utilize adaptive dynamics to investigate the evolutionary outcomes of the trade-off between transmission and virulence. Second, we perform a critical function analysis to generalize the results independent of specific trade-off assumptions and to determine the conditions for evolutionary stability and convergence stability. Last, we investigate the effects of different publicity measures on virulence evolution under two types of interactions, including the case of excess mortality alone and the coexistence of excess mortality and superinfection. Based on the general hypothesis of transmission virulence trade-off, we introduce the cost of host mobility caused by the scope and intensity of publicity. Numerical simulations present a set of evolutionary results, including continuously stable strategies, evolutionary branching points, repellers, and the Garden of Eden. Our results indicate that an excessive publicity scope and intensity can drive the epidemic evolution towards higher virulence. Both types of interactions suggest that continuously increasing the publicity scope under a low publicity intensity can effectively reduce virulence. Furthermore, the concurrent presence of excess mortality and superinfection induces the emergence of a higher virulence.